Delving Deeper into the Dilemma of Cytomorphological Deterioration due to Drying Artefact: Detailed Description of a Different Technique - a imran, AMBEREEN (Journal of Fatima Jinnah Medical University, 2018)
Background: Cytopathology has created a niche for itself in clinical laboratory medicine within the last few decades. It owes this momentous popularity to its ease, speed, cost effectiveness and reliability. But its reliability is critically dependent on certain factors. One of these is appropriate fixation. Two of the most commonly employed stains in cytopathology, namely Pap stain and Haematoxylin and Eosin, both require prompt wet fixation. Failure to do so seriously compromises the quality of cytomorphological features in smears. Since we face frequent interruptions in supply of ethanol, the most commonly used fixative, unfixed or improperly fixed smears are a frustration cytopathologists are all too familiar with, in our set up. Objective: To evaluate the utility of air-dried rehydrated smears and to compare them with routinely prepared wet-fixed smears. Materials and Methods: This study was carried out on 100 cases of FNAC carried out in Pathology Lab at Lahore GeneralHospital, Lahore. The processing was done in Pathology Department at Postgraduate Medical Institute, Lahore. It was a cross sectional study with non-probability purposive sampling. Three smears were taken from each case. One was wet fixed immediately. The other two were allowed to air dry. These were rehydrated by immersion in normal saline either within 30 minutes (Group 1) or 48 hours later (Group 2). They were then fixed and were all stained with Haematoxylin and Eosin. Slides were coded and reported. Later the results were decoded and analysed by Chi square test. Results: The only feature to exhibit statistically significant difference was the background RBC density. A cleaner background of Air–dried rehydrated smears was far more conducive in assessment of hemorrhagic aspirates, for example those from the thyroid, making it very easy to spot the aspirated cells. Cytomorphological features like cell border, cytoplasmic staining, nuclear border and chromatin staining did not exhibit statistically significant differences though some of these were marginally better visualized in Wet-fixed smears. Conclusion: Air drying followed by wet fixation was found to be a simple, inexpensive and reliable method. It can be adopted especially by tertiary care centres which cater to the needs of multiple peripheral centres. It is particularly helpful when dealing with haemorrhagic smearsand may be tried for such samples until techniques like Liquid Based Cytology become more widely available.